Kelayakan Usaha Perkebunan Melaleuca cajuputi subsp. cajuputi untuk Produksi Minyak Atsiri dan Produksi Madu (Feasibility of Melaleuca cajuput Plantation Business for Essential Oil Production and Honey Production) - Siti Wahyuningsih (Jurnal Penelitian Hutan Tanaman, 2023)
AbstractMelaleuca cajuput plantation is promising for cajuput oil production and apiculture. However, the economic potency of those businesses is not simultaneous because the tree will be pruned for oil which potentially reduces nutrient flow for honeybees. This study identifies the optimal time for leaf harvesting for oil production and apiculture and the economic value. A prediction of branch production (10.000 trees/ha) was calculated from the average branch numbers of 50 trees with intervals of 1 m x 1 m from three different sites. The business feasibility of cajuput oil production and apiculture was calculated based on the BC ratio, NPC, and DPP. The average number of branches is 6,500 (branches/ha). BC ratio for cajuput oil production and apiculture (10,000 trees/ha) and the NPV were 1.2 to 1.4; 1.2 and Rp 18,428,816 to 20,695,245; Rp 211,735, respectively. The cost recovery of investment for the cajuputi oil business and apiculture is 6 to 8 and 2 years, respectively. A combination of cajuput oil and apiculture is better to develop after the stand starts flowering at 1.5 years old and after the leaves can be harvested (1.5 to 4 years). However, the leaf harvesting could be held after the flowering season lasts from January to March.Keywords: Economic value, Melaleuca cajuputi, cajuput oil, honey AbstrakMelaleuca cajuputi menjanjikan untuk usaha minyak atsiri dan apikultur. Namun, potensi ekonomi dari kedua usaha tersebut tidak dapat diperoleh secara simultan, karena kayu putih akan dipangkas untuk produksi minyak atsiri yang juga akan mengurangi ketersediaan pakan bagi lebah madu. Penelitian ini bertujuan mengkaji waktu optimal panen daun kayu putih untuk minyak atsiri dan apikultur dan kelayakan usahanya. Pendugaan produksi cabang (10.000 pohon/ha) dihitung berdasar rerata jumlah cabang kayu putih dari 50 tanaman kayu putih berjarak tanam 1 m x 1 m dari tiga lokasi yang berbeda. Kelayakan usaha kayu putih untuk minyak atsiri dan apikultur dihitung berdasar nilai BC rasio, NPV dan DPP. Rerata jumlah cabang kayu putih adalah 6.500 (cabang/ha). BC rasio untuk produksi minyak kayu putih dan apikultur dari perkebunan kayu putih (10.000 pohon/ha) dan NPV masing-masing adalah 1,2-1,4; 1,2 dan Rp 18.428.816 - 20.695.245; Rp 211.735. DPP untuk bisnis minyak kayu putih dan apikultur masing-masing adalah 6-8 tahun dan 2 tahun. Kombinasi minyak kayu putih dan apikultur lebih baik dikembangkan setelah tegakan mulai berbunga pada umur 1,5 tahun dan setelah daun dapat dipanen (1,5-4 tahun). Namun, pemanenan daun sebaiknya dilakukan setelah musim berbunga berlangsung, yaitu dari Januari hingga Maret.Kata kunci: Nilai ekonomi, Melaleuca cajuputi, minyak astiri, madu